Embedding Gen-AI in cultural production and communication strategies. Qualitative analysis of 6 Lisbon based cases- study. - Foà, C. (10th STS Italia Conference, 2025)
Cultural production is a step of value creation process for cultural organizations and artists. These types of agents, however, follow different approaches concerning the strategic combination of creativity, management and communication, related to their mission, status, budget, workflows and market orientation. Some artists and cultural workers act as early adopters of new digital technologies, embracing entrepreneurial attitudes, collaborative and cocreative processes, but the overall cultural and creative sectors face multiple threats due to phenomena such as the platformization, datafication and the disappearing of cultural products (Duffy et al.,2019; Bilton; 2017) Platformization affects the cultural production increasing the focus of digital communication on interactivity, cocreation, personalization, storytelling and self-expression (Ouariach et al. 2023). Technological innovations, enhance the new communication paradigm (Cardoso, 2024), based on sharing and collaboration, but on the other pose threats to contents quality, IP, data and users’ protection rights, challenging both managers and specialists to retune their strategic and operational approaches to the field, adapting their workflows, tools, budgeting and stakeholders’ relationship. The rise of Gen-AI generated wide discussion about its benefits and FATE issues, being often represented a double-hedge sword for cultural production due to the potential enhancements in creativity and productivity and the risks for authorship, originality, output variety, job maintenance and perceived authenticity. Research shed light on Gen-AI usage by both cultural organizations and artists, however considering them separately lacks a comprehensive understanding of how the Gen-AI adoption by one type agent may influence the production process but also the stakeholders’ relationships and communication, mainly regarding to work of arts’ exhibition, marketing, and publics’ engagement strategies. Comparative cases-study includes six private and public cultural organizations, with different size, reputation, human, programming and economic resources and belonging to various sectors, ranging from performing and visual arts to audio-visual production and exhibition. Semi-structured interviews are conducted with two types of cultural workers communication managers and artists to understand if and how Gen-AI is directly adopted within their cultural production processes, and to what extent this strategy also affect strategic aspects related to the relationships with other cultural agents, their stakeholders, and the broad public. Thematic content analysis was conducted before triangulation of preliminary results. The main objective is to collect a variety of experiences to highlight both similarities and discrepancies in the strategies implemented to develop cultural production and communication flows. Conclusions highlight across analytic themes a set of: - heterogeneity of artists’ approach to Gen-AI on cultural production according to their sectors, careers’ stage and work of arts destination. - similarities among artist incipient usage of Gen-AI on their communication strategies; - similarities among organizations for what concerns the current reduced adoption of Gen-AI on their communication and cultural production, with growing curiosity and hesitations about the balance between benefits and thread of its adoption. Professionals are particularly concerned about IP of work of arts, standardization of communication contents and potential misuse by some internet users. On the other hand, professionals working in smaller organizations consider attractive the promise of reducing time-costly repetitive activities or improving their digital contents quality or data analysis competence.